303 Overview of Paternal Programming in Livestock Species. (21st September 2022) - Dahlen, Carl R; Caton, Joel S; Diniz, Wellison; Reynolds, Lawrence P; Ward, Alison K
Abstract: The concept of developmental programming from a maternal standpoint is well established. Perhaps even more impactful, however, is developmental programming that may arise from paternal contributions when single sires are responsible for breeding multiple females. Research in rodent models has shown that paternal obesity, high fat or low protein diets, exercise, stress, and drug and alcohol exposure can lead to epigenetic modifications in sperm and seminal plasma. Some of these changes withstand the extensive remodeling associated with fertilization and early embryo development, culminating in discernable offspring phenotypes that remain present for multiple generations. Certainly, the observations in rodent models related to alterations in offspring body weight, adiposity, metabolic responses, bone density, and reproductive outcomes and function have implications for the livestock industries if similar paternal programming phenomena exist. Livestock production systems are robust and dynamic and many paradigms exist with potential to alter male germ line epigenome, with specific changes likely related to timing of aberrant conditions relative to spermatogenesis and sperm residence in the epididymis. Within the context of routine management systems, our livestock patriarchs can experience major diet and weight changes, transportation and handling stress, environmental extremes, and/or changes in exercise duration, frequency, and intensity. In addition, livestock managers may embrace the concept of delivering specific quantities and types of feedstuffs, and apply other interventions if proven beneficial. Several research groups using livestock models have revealed that epigenetic machinery delivered in sperm and seminal plasma can be altered. A sheep model demonstrated the feeding rumen-protected methionine to rams from weaning to puberty resulted in epigenetic and phenotypic alterations still present in the F2 generation. This presentation will review the status of literature regarding paternal programming, identify knowledge gaps, and suggest areas for future research efforts with potential to enhance production efficiencies of livestock operations.